Extending Microsoft Dynamics 365 for finance and operations cookbook : enhance your business processes by building agile, secure, and scalable ERP solutions /: enhance your business processes by building agile, secure, and scalable ERP solutions. (2020) - (Technical architect), Buxton, Simon
No abstract available